Adsorption of dyes of different types on polyvinylformal-based porous sorbents - Siryk О.О.; Samchenko, Yu.M.; Poltoratska, T.P.; Kryklya, S.O.; Trofimchuk А.К. (Reports of the National Academy of Sciences of Ukraine, 2019)
This paper deals with the study of the adsorption properties of polyvinylformal (PVF). A highly porous sponge sorbent based on polyvinylformal, as well as filled sorbents with additives of carbon nanotubes, laponite, and aminopropyl aerosil (APA), is synthesized. The adsorption patterns on the obtained sorbents for different dyes (cationic — methyl violet, anionic — azorubine, and non-ionic — nigrosine) are studied. It is established that the polyvinylformal sorbent removes azorubine at pH < 4 and methyl violet at pH > 4. Аdsorption equilibrium for all sorbents during the sorption of dyes is reached in 15-30 min. PVF filled with aminopropyl aerosil showed the highest sorption capacity toward azorubine and nigrosine and amounts to 11.4 and 7.1 mg/g, respectively, for methyl violet — unfilled PVF (5.0 mg/g). The kinetic measurements for all the composites and dyes indicate that the adsorption process follows the pseudo-second order kinetics. To describe the obtained adsorption isotherms of methyl violet on all sorbents and azorubine on pure PVF and PVF-APA, the Langmuir theoretical model fits better. In the case of nigrosine on all sorbents and azorubine on PVF filled with carbon nanotubes and laponite, the Freundlich model is preferable.